Composite roll core cigarette filter tip and preparation method thereof
By winding flexible aerogel sheets loaded with ZIF-8@AC and electrospun membranes of CeO2-MnO2, the problem of poor filtration of gaseous harmful substances in cigarette filters was solved, achieving a highly efficient synergistic effect of adsorption and catalysis, improving the removal capacity of harmful substances and maintaining the smoothness of smoking.
Patent Information
- Application Number
- CN202511786160.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-01
- Publication Date
- 2026-01-23
AI Technical Summary
Existing cigarette filters have limitations in filtering harmful substances, especially in filtering harmful gaseous components. They also suffer from uneven dispersion of functional materials, limited loading capacity, low contact efficiency with smoke, and increased draw resistance.
Flexible aerogel sheets loaded with ZIF-8@AC and electrospun membranes loaded with CeO2-MnO2 are wound and thermally bonded together. Through adsorption-catalysis synergy and a wound multi-level pore design, the contact path between flue gas and functional materials is extended.
It improves the overall filtration efficiency for harmful substances, especially the removal of tar, polycyclic aromatic hydrocarbons, hydrogen cyanide, volatile aldehydes and ketones, and reactive oxygen free radicals, while maintaining a smooth smoking experience.
Abstract
Description
Technical Field
[0001] This invention relates to the field of cigarette filter manufacturing technology, specifically to a composite core cigarette filter and its preparation method. Background Technology
[0002] Cigarettes produce a wide variety of harmful substances during combustion, including tar, nicotine, carbon monoxide, gaseous free radicals, polycyclic aromatic hydrocarbons, volatile aldehydes and ketones, and hydrogen cyanide. These substances not only enter the body through the smoker's respiratory system, causing continuous damage to their cardiopulmonary function, nervous system, and immune system, increasing the risk of lung cancer and cardiovascular disease, but also diffuse into the surrounding environment as sidestream smoke, creating secondhand smoke pollution and posing a serious threat to the health of non-smokers.
[0003] As a core component of cigarette harm reduction systems, the filter tip's structural design and material properties directly determine its efficiency in trapping harmful substances. Current cigarette filters primarily use cellulose acetate tow bonded together with plasticizers. They capture particulate matter such as tar through mechanical trapping between fibers and remove some large-molecule harmful substances through diffusion adsorption. However, this structure has significant limitations in filtering harmful gaseous components. Existing technologies typically add functional materials to the filter tip to improve filtration efficiency, such as activated carbon (AC), zeolite, and metal oxides. Activated carbon, with its large specific surface area, has good adsorption capacity for various organic compounds, but its adsorption capacity is limited, it is easily saturated, and its capture effect on free radicals and other reactive substances is poor. While some metal oxides (such as CeO2 and MnO2) possess catalytic oxidation properties and can catalytically degrade some harmful gases and free radicals, their typically small specific surface area and short contact time with smoke make it difficult to fully exert their effects. Physically mixing adsorbent and catalytic materials and filling them into the filter cavity or dispersing them in the fiber bundle often results in problems such as uneven material dispersion, limited load, low contact efficiency with flue gas, and increased suction resistance.
[0004] Therefore, developing a novel composite filter structure that can efficiently integrate adsorption and catalysis functions and ensure full and orderly contact between flue gas and functional materials is key to achieving efficient harm reduction. Summary of the Invention
[0005] The technical problem to be solved: The purpose of this invention is to provide a composite cigarette filter tip and its preparation method. It is formed by winding and thermally bonding a flexible aerogel sheet loaded with ZIF-8@AC and an electrospun membrane loaded with CeO2-MnO2. Through the synergistic effect of "adsorption-catalysis" and the winding multi-level pore design, the contact path between smoke and functional materials is extended, thereby improving the overall filtration efficiency of harmful substances.
[0006] Technical solution: A composite cigarette filter tip, wherein the filter tip is formed by winding and thermally bonding a composite structure, the composite structure comprising a flexible aerogel sheet and an electrospun membrane deposited on the surface, the flexible aerogel sheet containing ZIF-8@AC porous adsorbent material, and the electrospun membrane being loaded with CeO2-MnO2 degradation material.
[0007] The above-mentioned method for preparing composite cigarette filter tips includes the following steps: S1. Prepare a cellulose nanofiber dispersion, add ZIF-8@AC to it, disperse with ultrasonic assistance, add silane coupling agent, stir and mix evenly to obtain an aerogel precursor dispersion, pour the dispersion into a mold, and after static aging, pre-freezing and freeze-drying, obtain a flexible aerogel sheet. S2. Dissolve cellulose acetate in a mixed solvent of acetone and N,N-dimethylacetamide, add CeO2-MnO2 to it, and stir until completely dispersed to obtain a homogeneous spinning solution; S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun and directly deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0008] Preferably, the preparation method of ZIF-8@AC includes the following steps: S11. Place activated carbon in an acidic solution and stir to react. After the reaction is complete, wash until neutral and dry to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution; S13. Add the porous AC from step S11 to the metal source solution, sonicate to wet, and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. Transfer the suspension to a high-pressure reactor and heat to react, to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0009] Preferably, the preparation method of CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, adjust the pH to alkaline with ammonia water to form a suspension; S22. Transfer the suspension to a high-pressure reactor, heat and react to obtain a precipitate; S23. Cool, wash, dry, and calcine the precipitate to obtain CeO2-MnO2.
[0010] Preferably, in step S1, the concentration of the cellulose nanofiber dispersion is 0.5-3 wt%, the aspect ratio of the nanofibers is 50-300:1, the silane coupling agent is one or more of 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane or vinyltrimethoxysilane, the concentration of ZIF-8@AC in the aerogel precursor dispersion is 2-10 wt%, the concentration of the silane coupling agent is 0.5-3 wt%, and the thickness of the aerogel sheet is 0.5-1 mm.
[0011] Preferably, in step S2, the volume ratio of acetone to N,N-dimethylacetamide is 2-1:1, the concentration of cellulose acetate in the spinning solution is 16-20 wt%, the concentration of CeO2-MnO2 is 5-10 wt%, and in step S3, the electrospinning voltage is 15-25 kV, the collection distance is 10-20 cm, and the humidity is 60-80%.
[0012] Preferably, in step S11, the acidic solution is a 1-3 mol / L HNO3 solution, the stirring temperature is 60-90℃, and the reaction time is 2-6 h; in step S12, the concentration of the metal source solution is 0.05-0.15 mol / L, the concentration of the organic ligand solution is 0.2-0.6 mol / L; in step S13, the concentration of porous AC is 1-5 wt% of the total mass of the suspension, the molar ratio of the metal source to the organic ligand in the suspension is 1:4-8, the temperature of the high-pressure reactor is 80-120℃, and the reaction time is 4-12 h.
[0013] Preferably, in step S21, the molar ratio of Ce(NO3)3·6H2O to potassium permanganate is 1:1~3, and the pH value is adjusted to 9~11; in step S22, the temperature of the high-pressure reactor is 120~140℃, and the reaction time is 12~18h; in step S23, the calcination temperature is 350~450℃, and the time is 2~4h.
[0014] Beneficial effects: The composite core cigarette filter of the present invention has the following advantages: In this invention, flexible aerogel sheets with high porosity and a three-dimensional network structure provide abundant channels and a large specific surface area for flue gas passage. The ZIF-8@AC porous adsorbent material loaded on the aerogel framework combines the excellent physical adsorption properties of AC with the precise pore size sieving and large specific surface area of ZIF-8, which can efficiently capture large molecular particles such as tar and polycyclic aromatic hydrocarbons, as well as small molecule polar poisons such as hydrogen cyanide, acetaldehyde, and acrolein in the flue gas. The aerogel framework not only ensures the uniform dispersion and fixation of the ZIF-8@AC material, but its own porous structure also plays a role in adsorbing and prolonging the contact time of flue gas, thereby improving the overall adsorption capacity and filtration efficiency of the filter tip for particulate harmful substances.
[0015] In this invention, a nanofiber membrane is deposited on the surface of an aerogel sheet using electrospinning technology, in which the CeO2-MnO2 degradation catalyst is loaded in a highly dispersed state within a fiber network with a large specific surface area. A synergistic catalytic effect is formed between CeO2 and MnO2 through interfacial electron transfer. CeO2 provides reactive oxygen species, while MnO2, as a highly efficient oxidation reaction active center, can efficiently degrade carbon monoxide, hydrogen cyanide, and volatile aldehydes and ketones such as formaldehyde and acetaldehyde. It also has a strong ability to scavenge reactive oxygen free radicals present in flue gas. The electrospinned membrane increases the contact opportunities between the catalyst and the flue gas, avoiding the problem of easy saturation from simple physical adsorption, and achieving deep purification of gaseous toxic substances that are difficult to remove with traditional filters.
[0016] This invention combines a flexible aerogel sheet with a surface electrospun film and then winds it into a core to form continuous and orderly channels. The "adsorption-degradation" tandem synergy and the winding structure extend the reaction path, making the interaction between smoke and functional materials more thorough. The structure is thermally bonded to form a whole, which has good mechanical strength and can control the suction resistance within a suitable range, ensuring a smooth smoking experience. Detailed Implementation
[0017] The present invention will be further described below with reference to embodiments. These embodiments are illustrative of the present invention, but the present invention is not limited to these embodiments: Example 1
[0018] A method for preparing a composite cigarette filter includes the following steps: S1. Prepare a 0.5 wt% cellulose nanofiber dispersion with an aspect ratio of 100 ± 50:1. Add ZIF-8@AC to the dispersion and disperse it with ultrasonic assistance. Then add 3-glycidoxypropyltrimethoxysilane and stir to mix evenly to obtain an aerogel precursor dispersion. The concentration of ZIF-8@AC in the dispersion is 2 wt%, and the concentration of 3-glycidoxypropyltrimethoxysilane is 0.5 wt%. Pour the dispersion into a mold, allow it to stand for aging, pre-freeze it, and freeze-dry it at -60℃ and 0.1 Pa for 24 h to obtain a flexible aerogel sheet with a thickness of 0.5 mm. S2. Dissolve cellulose acetate in a mixed solvent of acetone and N,N-dimethylacetamide in a volume ratio of 1:1, add CeO2-MnO2, and stir until completely dispersed to obtain a homogeneous spinning solution. The concentration of cellulose acetate in the spinning solution is 16 wt%, and the concentration of CeO2-MnO2 is 10 wt%. S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun at a voltage of 15kV, a collection distance of 10cm, and a humidity of 65±5%, and deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0019] The preparation method of ZIF-8@AC mentioned above includes the following steps: S11. Activated carbon was placed in a 1 mol / L HNO3 solution and stirred at 90℃ for 2 h. After the reaction was completed, it was washed until neutral and dried to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution with a concentration of 0.05 mol / L, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution with a concentration of 0.2 mol / L. S13. Add the porous AC from step S11 to the metal source solution, sonicate and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. The molar ratio of metal source to organic ligand in the suspension is 1:4, and the concentration of AC is 1wt%. Transfer the suspension to a high-pressure reactor and react at 80℃ for 12h to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0020] The above method for preparing CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, with a molar ratio of Ce(NO3)3·6H2O to potassium permanganate of 1:1. Adjust the pH to 9 with ammonia water to form a suspension. S22. Transfer the suspension to a high-pressure reactor and react at 120°C for 18 hours. Heating the reaction yields a precipitate. S23. The precipitate was cooled, washed, dried, and calcined at 350℃ for 4 hours to obtain CeO2-MnO2.
[0021] Example 2
[0022] A method for preparing a composite cigarette filter includes the following steps: S1. Prepare a 3wt% cellulose nanofiber dispersion with an aspect ratio of 250±50:1. Add ZIF-8@AC to the dispersion and disperse it with ultrasonic assistance. Then add 3-aminopropyltriethoxysilane and stir to mix evenly to obtain an aerogel precursor dispersion. The concentration of ZIF-8@AC in the dispersion is 10wt% and the concentration of 3-aminopropyltriethoxysilane is 3wt%. Pour the dispersion into a mold, allow it to stand for aging, pre-freeze it, and freeze-dry it at -40℃ and 10Pa for 48h to obtain a flexible aerogel sheet with a thickness of 1mm. S2. Dissolve cellulose acetate in a mixed solvent of propionate and N,N-dimethylacetamide in a volume ratio of 2:1, add CeO2-MnO2, and stir until completely dispersed to obtain a homogeneous spinning solution. The concentration of cellulose acetate in the spinning solution is 20 wt%, and the concentration of CeO2-MnO2 is 5 wt%. S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun at a voltage of 25kV, a collection distance of 20cm, and a humidity of 70±10%, and deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0023] The preparation method of ZIF-8@AC mentioned above includes the following steps: S11. Activated carbon was placed in a 3 mol / L HNO3 solution and stirred at 60℃ for 6 h. After the reaction was completed, it was washed until neutral and dried to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution with a concentration of 0.15 mol / L, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution with a concentration of 0.6 mol / L. S13. Add the porous AC from step S11 to the metal source solution, sonicate and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. The molar ratio of metal source to organic ligand in the suspension is 1:8, and the concentration of AC is 5wt%. Transfer the suspension to a high-pressure reactor and react at 120℃ for 4h to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0024] The above method for preparing CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, with a molar ratio of Ce(NO3)3·6H2O to potassium permanganate of 1:3. Adjust the pH to 11 with ammonia water to form a suspension. S22. Transfer the suspension to a high-pressure reactor and react at 140°C for 12 hours. Heating the reaction yields a precipitate. S23. The precipitate was cooled, washed, dried, and calcined at 450℃ for 2 hours to obtain CeO2-MnO2.
[0025] Example 3
[0026] A method for preparing a composite cigarette filter includes the following steps: S1. Prepare a 2wt% cellulose nanofiber dispersion with an aspect ratio of 150±50:1. Add ZIF-8@AC to the dispersion and disperse it with ultrasonic assistance. Then add 3-glycidoxypropyltrimethoxysilane and stir to mix evenly to obtain an aerogel precursor dispersion. The concentration of ZIF-8@AC in the dispersion is 7wt% and the concentration of 3-glycidoxypropyltrimethoxysilane is 1.5wt%. Pour the dispersion into a mold, allow it to stand for aging, pre-freeze it, and freeze-dry it at -60℃ and 0.1Pa for 30h to obtain a flexible aerogel sheet with a thickness of 0.6mm. S2. Dissolve cellulose acetate in a mixed solvent of propionate and N,N-dimethylacetamide in a volume ratio of 2:1, add CeO2-MnO2, and stir until completely dispersed to obtain a homogeneous spinning solution. The concentration of cellulose acetate in the spinning solution is 18 wt%, and the concentration of CeO2-MnO2 is 8 wt%. S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun at a voltage of 18kV, a collection distance of 20cm, and a humidity of 70±5%, and deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0027] The preparation method of ZIF-8@AC mentioned above includes the following steps: S11. Activated carbon was placed in a 2 mol / L HNO3 solution and stirred at 80℃ for 4 h. After the reaction was completed, it was washed until neutral and dried to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution with a concentration of 0.1 mol / L, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution with a concentration of 0.4 mol / L. S13. Add the porous AC from step S11 to the metal source solution, sonicate and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. The molar ratio of metal source to organic ligand in the suspension is 1:6, and the concentration of AC is 3wt%. Transfer the suspension to a high-pressure reactor and react at 100℃ for 8 hours to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0028] The above method for preparing CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, with a molar ratio of Ce(NO3)3·6H2O to potassium permanganate of 1:2. Adjust the pH to 9 with ammonia water to form a suspension. S22. Transfer the suspension to a high-pressure reactor and react at 120°C for 12 hours. Heating the reaction yields a precipitate. S23. The precipitate was cooled, washed, dried, and calcined at 380℃ for 3 hours to obtain CeO2-MnO2.
[0029] Example 4
[0030] A method for preparing a composite cigarette filter includes the following steps: S1. Prepare a 2wt% cellulose nanofiber dispersion with an aspect ratio of 150±50:1. Add ZIF-8@AC to the dispersion and disperse it with ultrasonic assistance. Then add 3-glycidoxypropyltrimethoxysilane and stir to mix evenly to obtain an aerogel precursor dispersion. The concentration of ZIF-8@AC in the dispersion is 6wt% and the concentration of 3-glycidoxypropyltrimethoxysilane is 1.5wt%. Pour the dispersion into a mold, allow it to stand for aging, pre-freeze it, and freeze-dry it at -60℃ and 0.1Pa for 30h to obtain a flexible aerogel sheet with a thickness of 0.6mm. S2. Dissolve cellulose acetate in a mixed solvent of propionate and N,N-dimethylacetamide in a volume ratio of 2:1, add CeO2-MnO2, and stir until completely dispersed to obtain a homogeneous spinning solution. The concentration of cellulose acetate in the spinning solution is 18 wt%, and the concentration of CeO2-MnO2 is 9 wt%. S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun at a voltage of 18kV, a collection distance of 20cm, and a humidity of 70±5%, and deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0031] The preparation method of ZIF-8@AC mentioned above includes the following steps: S11. Activated carbon was placed in a 2 mol / L HNO3 solution and stirred at 80℃ for 4 h. After the reaction was completed, it was washed until neutral and dried to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution with a concentration of 0.1 mol / L, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution with a concentration of 0.4 mol / L. S13. Add the porous AC from step S11 to the metal source solution, sonicate and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. The molar ratio of metal source to organic ligand in the suspension is 1:6, and the concentration of AC is 3wt%. Transfer the suspension to a high-pressure reactor and react at 100℃ for 8 hours to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0032] The above method for preparing CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, with a molar ratio of Ce(NO3)3·6H2O to potassium permanganate of 1:2. Adjust the pH to 9 with ammonia water to form a suspension. S22. Transfer the suspension to a high-pressure reactor and react at 120°C for 12 hours. Heating the reaction yields a precipitate. S23. The precipitate was cooled, washed, dried, and calcined at 380℃ for 3 hours to obtain CeO2-MnO2.
[0033] Example 5
[0034] A method for preparing a composite cigarette filter includes the following steps: S1. Prepare a 2wt% cellulose nanofiber dispersion with an aspect ratio of 150±50:1. Add ZIF-8@AC to the dispersion and disperse it with ultrasonic assistance. Then add 3-glycidoxypropyltrimethoxysilane and stir to mix evenly to obtain an aerogel precursor dispersion. The concentration of ZIF-8@AC in the dispersion is 9wt% and the concentration of 3-glycidoxypropyltrimethoxysilane is 1.5wt%. Pour the dispersion into a mold, allow it to stand for aging, pre-freeze it, and freeze-dry it at -60℃ and 0.1Pa for 30h to obtain a flexible aerogel sheet with a thickness of 0.7mm. S2. Dissolve cellulose acetate in a mixed solvent of propionate and N,N-dimethylacetamide in a volume ratio of 2:1, add CeO2-MnO2, and stir until completely dispersed to obtain a homogeneous spinning solution. The concentration of cellulose acetate in the spinning solution is 18 wt%, and the concentration of CeO2-MnO2 is 6 wt%. S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun at a voltage of 18kV, a collection distance of 20cm, and a humidity of 70±5%, and deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0035] The preparation method of ZIF-8@AC mentioned above includes the following steps: S11. Activated carbon was placed in a 2 mol / L HNO3 solution and stirred at 80℃ for 4 h. After the reaction was completed, it was washed until neutral and dried to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution with a concentration of 0.1 mol / L, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution with a concentration of 0.4 mol / L. S13. Add the porous AC from step S11 to the metal source solution, sonicate and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. The molar ratio of metal source to organic ligand in the suspension is 1:6, and the concentration of AC is 3wt%. Transfer the suspension to a high-pressure reactor and react at 100℃ for 8 hours to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0036] The above method for preparing CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, with a molar ratio of Ce(NO3)3·6H2O to potassium permanganate of 1:2. Adjust the pH to 9 with ammonia water to form a suspension. S22. Transfer the suspension to a high-pressure reactor and react at 120°C for 12 hours. Heating the reaction yields a precipitate. S23. The precipitate was cooled, washed, dried, and calcined at 380℃ for 3 hours to obtain CeO2-MnO2.
[0037] Example 6
[0038] A method for preparing a composite cigarette filter includes the following steps: S1. Prepare a 1.5 wt% cellulose nanofiber dispersion with an aspect ratio of 150 ± 50:1. Add ZIF-8@AC to the dispersion and disperse it with ultrasonic assistance. Then add 3-glycidoxypropyltrimethoxysilane and stir to mix evenly to obtain an aerogel precursor dispersion. The concentration of ZIF-8@AC in the dispersion is 7 wt% and the concentration of 3-glycidoxypropyltrimethoxysilane is 1.5 wt%. Pour the dispersion into a mold, allow it to stand for aging, pre-freeze it, and freeze-dry it at -60℃ and 0.1 Pa for 30 h to obtain a flexible aerogel sheet with a thickness of 0.6 mm. S2. Dissolve cellulose acetate in a mixed solvent of propionate and N,N-dimethylacetamide in a volume ratio of 2:1, add CeO2-MnO2, and stir until completely dispersed to obtain a homogeneous spinning solution. The concentration of cellulose acetate in the spinning solution is 18 wt%, and the concentration of CeO2-MnO2 is 8 wt%. S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun at a voltage of 18kV, a collection distance of 20cm, and a humidity of 70±5%, and deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
[0039] The preparation method of ZIF-8@AC mentioned above includes the following steps: S11. Activated carbon was placed in a 2 mol / L HNO3 solution and stirred at 80℃ for 4 h. After the reaction was completed, it was washed until neutral and dried to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution with a concentration of 0.1 mol / L, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution with a concentration of 0.4 mol / L. S13. Add the porous AC from step S11 to the metal source solution, sonicate and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. The molar ratio of metal source to organic ligand in the suspension is 1:6, and the concentration of AC is 3wt%. Transfer the suspension to a high-pressure reactor and react at 100℃ for 8 hours to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
[0040] The above method for preparing CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, with a molar ratio of Ce(NO3)3·6H2O to potassium permanganate of 1:2. Adjust the pH to 9 with ammonia water to form a suspension. S22. Transfer the suspension to a high-pressure reactor and react at 120°C for 12 hours. Heating the reaction yields a precipitate. S23. The precipitate was cooled, washed, dried, and calcined at 380℃ for 3 hours to obtain CeO2-MnO2.
[0041] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that the flexible aerogel sheet of Comparative Example 1 does not contain ZIF-8@AC, while the rest of the preparation steps and parameters are exactly the same as those of Example 3.
[0042] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that the aerogel precursor dispersion of Comparative Example 2 contains 7 wt% AC and does not contain ZIF-8@AC, while the rest of the preparation steps and parameters are exactly the same as those of Example 3.
[0043] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that the aerogel precursor dispersion of Comparative Example 3 contains 7 wt% ZIF-8 but does not contain ZIF-8@AC. The remaining preparation steps and parameters are exactly the same as those of Example 3.
[0044] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that the electrospun film of Comparative Example 4 does not contain CeO2-MnO2, while the rest of the preparation steps and parameters are exactly the same as those of Example 3.
[0045] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that the spinning solution of Comparative Example 5 contains 8 wt% MnO2, while the remaining preparation steps and parameters are exactly the same as those of Example 3.
[0046] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that the filter tip of Comparative Example 6 is only made of loaded ZIF-8@AC wound together, while the rest of the preparation steps and parameters are exactly the same as those of Example 3.
[0047] Comparative Example 7 The difference between Comparative Example 7 and Example 3 is that the filter tip of Comparative Example 7 is an electrospun membrane with CeO2-MnO2 deposited on the surface of a common filter tip.
[0048] Comparative Example 8 The difference between Comparative Example 8 and Example 3 is that the filter of Comparative Example 8 is a common filter on the market.
[0049] Comparative Example 9 The difference between Comparative Example 9 and Example 3 is that the adsorbent loaded in the aerogel sheet of Comparative Example 9 is a physically mixed ZIF-8 and AC powder, and the mass ratio of the two is the same as that of ZIF-8 and AC in the ZIF-8@AC composite material in Example 3. The other preparation steps and parameters are exactly the same as those in Example 3.
[0050] Testing: Total particulate matter (tar) rejection rate test reference standard GB / T 19609-2024; CO rejection rate test reference standard GB / T 23356-2024; Aldehyde rejection rate is detected by liquid chromatography; Hydrogen cyanide rejection rate is detected by ion chromatography; Free radicals are detected by electron spin resonance method; Absorption resistance and filter rod ventilation rate test reference standard GB / T 22838; Cigarette specifications are 84mm in length (54mm tobacco material segment + 30mm filter rod segment, cigarette circumference 17.0mm, and the weight of tobacco material segment in the cigarette is 0.40±0.1g).
[0051] Table 1 Filtration efficiency test Total particulate matter (tar) retention rate (%) CO2 rejection rate (%) Aldehyde Retention Rate (%) Hydrogen cyanide rejection rate (%) Free radical scavenging rate (%) Example 1 58.5 45.2 62.1 65.9 78.6 Example 2 60.5 46.8 64.3 67.1 80.4 Example 3 62.3 48.5 66.7 69.4 82.3 Example 4 59.8 46.0 63.5 66.3 79.2 Example 5 61.0 47.2 65.0 67.4 80.4 Example 6 59.5 45.8 63.0 65.5 78.6 Comparative Example 1 40.1 25.3 38.5 42.2 45.7 Comparative Example 2 53.7 35.6 50.2 55.1 62.3 Comparative Example 3 48.5 32.1 46.8 49.5 58.9 Comparative Example 4 55.2 30.8 52.4 58.3 60.7 Comparative Example 5 56.8 38.5 54.1 59.6 65.9 Comparative Example 6 56.2 28.4 40.2 44.6 50.9 Comparative Example 7 42.0 32.6 53.8 57.9 63.1 Comparative Example 8 38.5 18.9 35.6 39.7 42.5 Comparative Example 9 54.5 36.2 51.7 56.1 64.0 In this invention, the high adsorption performance of the ZIF-8@AC composite material, the synergistic degradation effect of the CeO2-MnO2 catalyst, and the path extension effect brought about by the winding structure jointly achieve multi-level and multi-mechanism purification of harmful substances in flue gas. The filtration efficiencies of Comparative Examples 1 and 8 are significantly lower than those of the Example, indicating that traditional filter structures lacking functional adsorption and catalytic materials, relying solely on mechanical interception and simple adsorption, cannot effectively address gaseous harmful substances and active free radicals in flue gas. Comparative Example 2 only adds AC, utilizing its porous structure to adsorb some small organic molecules, but the specific surface area of activated carbon is limited and easily saturated, affecting the adsorption effect. Comparative Example 3 only uses... ZIF-8, with its regular pores and high specific surface area, exhibits strong selective adsorption of small molecules, improving filtration efficiency compared to AC. However, it lacks synergistic effects and is insufficient for standalone application. Comparative Example 4, lacking CeO2-MnO2, lacks catalytic decomposition capabilities. Comparative Example 5, using only CeO2, possesses oxygen vacancies and redox properties, but CeO2 is prone to aggregation, affecting degradation efficiency. Comparative Examples 6 and 7 demonstrate that only by combining flexible aerogel sheets with surface electrospun membranes and then winding them into a core can a synergistic "adsorption-degradation" effect be achieved. In Comparative Example 9, the physically mixed adsorbent material exhibits poor dispersion uniformity within the aerogel framework, easily leading to aggregation and reducing overall filtration efficiency.
[0052] Table 2. Suction Resistance and Ventilation Rate Tests Suction resistance (kPa) Filter rod ventilation rate (%) Example 1 1.27 39.56 Example 2 1.49 34.71 Example 3 1.35 37.82 Example 4 1.38 36.95 Example 5 1.42 35.64 Example 6 1.37 37.2 Comparative Example 1 1.29 38.61 Comparative Example 2 1.38 37.18 Comparative Example 3 1.34 37.62 Comparative Example 4 1.30 41.17 Comparative Example 5 1.34 38.76 Comparative Example 6 1.29 32.89 Comparative Example 7 1.24 42.15 Comparative Example 8 1.23 46.68 Comparative Example 9 1.52 33.47 In the embodiments of this invention, the suction resistance is within a reasonable range suitable for a pleasant smoking experience. Through the high porosity of the aerogel and the nanofiber network of the electrospun membrane, while increasing the contact path of harmful substances, the airflow resistance is not significantly increased, ensuring a smooth smoking experience. The ventilation rates of the embodiments are all lower than those of the commercially available ordinary filter tip in Comparative Example 8, indicating that the structure of this invention has a stronger retention effect on smoke, which is beneficial for prolonging the contact time between smoke and functional materials and improving filtration efficiency. Comparative Example 1 (without ZIF-8@AC) and Comparative Example 4 (without CeO2-MnO2) have higher ventilation rates, further confirming that the introduction of functional materials increases the complexity of the smoke path. Although it reduces the ventilation rate, it enhances the purification effect. Comparative Example 2 uses the original AC, which, although having a large specific surface area, has a wide pore size distribution, which helps to select for small-molecule polar harmful substances in the smoke. The selective adsorption capacity is limited; although the single ZIF-8 material in Comparative Example 3 performs well in the adsorption of certain small molecules, its overall adsorption capacity is not as good as that of the ZIF-8@AC composite material; Comparative Example 5 is only loaded with MnO2, the effective reaction path of flue gas in the filter is relatively short, and the ventilation is relatively high, but the overall purification effect is weaker than the composite catalytic system described in this invention; Comparative Example 6 relies solely on ZIF-8@AC and lacks the catalytic degradation functional layer to transform harmful substances in the gas phase, resulting in increased airflow resistance and reduced ventilation rate; Comparative Example 7 lacks a high-porosity aerogel as an adsorption substrate and flue gas distribution layer, and it is difficult to effectively prolong the contact time between flue gas and functional materials by relying solely on the surface catalytic film; The physically mixed adsorption material in Comparative Example 9 has poor dispersion uniformity in the aerogel skeleton, is prone to agglomeration, leading to local pore blockage and increased airflow resistance.
[0053] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A composite core cigarette filter, characterized in that, The filter tip is a single unit formed by winding and thermally bonding a composite structure, the composite structure including a flexible aerogel sheet. The flexible aerogel sheet contains ZIF-8@AC porous adsorbent material and is deposited on the surface of the electrospun membrane. The electrospun membrane is loaded with CeO2-MnO2 degradation material.
2. The method for preparing a composite cigarette filter according to claim 1, characterized in that, Includes the following steps: S1. Prepare a cellulose nanofiber dispersion, add ZIF-8@AC to it, disperse with ultrasonic assistance, add silane coupling agent, stir and mix evenly to obtain an aerogel precursor dispersion, pour the dispersion into a mold, and after static aging, pre-freezing and freeze-drying, obtain a flexible aerogel sheet. S2. Dissolve cellulose acetate in a mixed solvent of acetone and N,N-dimethylacetamide, add CeO2-MnO2 to it, and stir until completely dispersed to obtain a homogeneous spinning solution; S3. Using the flexible aerogel sheet obtained in step S1 as the receiving substrate, the spinning solution obtained in step S2 is electrospun and directly deposited on the surface of the flexible aerogel sheet to obtain a composite structure. S4. The composite structure obtained in step S3 is wound into a bundle and then thermally bonded to obtain a composite cigarette filter.
3. The method for preparing a composite cigarette filter according to claim 2, characterized in that, The preparation method of ZIF-8@AC includes the following steps: S11. Place activated carbon in an acidic solution and stir to react. After the reaction is complete, wash until neutral and dry to obtain porous AC. S12. Dissolve Zn(NO3)2·6H2O in water or methanol to obtain a metal source solution, and dissolve 2-methylimidazole in water or methanol to obtain an organic ligand solution; S13. Add the porous AC from step S11 to the metal source solution, sonicate to wet, and then add the organic ligand solution to the mixture under vigorous stirring to obtain a suspension. Transfer the suspension to a high-pressure reactor and heat to react, to obtain a crude ZIF-8@AC solution. S14. The crude ZIF-8@AC solution was naturally cooled, washed, centrifuged, and dried to obtain the ZIF-8@AC porous adsorbent material.
4. The method for preparing a composite cigarette filter according to claim 2, characterized in that, The preparation method of CeO2-MnO2 includes the following steps: S21. Dissolve Ce(NO3)3·6H2O and potassium permanganate in water, adjust the pH to alkaline with ammonia water to form a suspension; S22. Transfer the suspension to a high-pressure reactor, heat and react to obtain a precipitate; S23. Cool, wash, dry, and calcine the precipitate to obtain CeO2-MnO2.
5. The method for preparing a composite cigarette filter according to claim 2, characterized in that, In step S1, the concentration of the cellulose nanofiber dispersion is 0.5-3 wt%, the aspect ratio of the nanofibers is 50-300:1, the silane coupling agent is one or more of 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane or vinyltrimethoxysilane, the concentration of ZIF-8@AC in the aerogel precursor dispersion is 2-10 wt%, the concentration of the silane coupling agent is 0.5-3 wt%, and the thickness of the aerogel sheet is 0.5-1 mm.
6. The method for preparing a composite cigarette filter according to claim 2, characterized in that, In step S2, the volume ratio of acetone to N,N-dimethylacetamide is 2-1:1, the concentration of cellulose acetate in the spinning solution is 16-20 wt%, the concentration of CeO2-MnO2 is 5-10 wt%, and the electrospinning voltage in step S3 is 15-25 kV, the collection distance is 10-20 cm, and the humidity is 60-80%.
7. The method for preparing a composite cigarette filter according to claim 3, characterized in that, In step S11, the acidic solution is a 1-3 mol / L HNO3 solution, the stirring temperature is 60-90℃, and the reaction time is 2-6 h. In step S12, the concentration of the metal source solution is 0.05-0.15 mol / L, and the concentration of the organic ligand solution is 0.2-0.6 mol / L. In step S13, the concentration of porous AC is 1-5 wt% of the total mass of the suspension, the molar ratio of the metal source to the organic ligand in the suspension is 1:4-8, the temperature of the high-pressure reactor is 80-120℃, and the reaction time is 4-12 h.
8. The method for preparing a composite cigarette filter according to claim 4, characterized in that, In step S21, the molar ratio of Ce(NO3)3·6H2O to potassium permanganate is 1:1~3, and the pH value is adjusted to 9~11. In step S22, the temperature of the high-pressure reactor is 120~140℃, and the reaction time is 12~18h. In step S23, the calcination temperature is 350~450℃, and the time is 2~4h.